Mapping digital media: France - Koc-Michalska, Karolina; Vedel, Thierry (New York, 2013)
"According to standard indicators, the transition to digital media in France has been a success. By the end of 2011, digital switch-over of television was complete and more than two-thirds of the population was online. Earlier that year, however, a survey revealed that more people thought the quality of media output had declined in recent years compared to those who thought it had improved, and this tendency was still present in 2013. While the funding crisis in print is due to loss of advertising revenue, the funding crisis in public service broadcasting has been linked to increased politicization. Th e proliferation of niche outlets online, meanwhile, is overshadowed by their limited reach and uncertain future. At the receiving end, audiences have demonstrated a strong appetite for new media delivery technologies. High-defi nition television sets have reached three-quarters of households, while 13 percent of those listening to the radio now do so via the internet. But in contrast to a relatively painless and swift digital transition in television, the switch-over process for radio has stalled due to a lack of both political and commercial will. ..."